2000
DOI: 10.1097/00008483-200011000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Performance and Training in Cardiac Patients With Atrial Fibrillation

Abstract: Exercise training significantly improves exercise performance in cardiac patients with AF. AF affects exercise performance but does not impair the beneficial effects of training. Patients with chronic AF should therefore not be dissuaded from participating in exercise training after a cardiac event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
6
22
0
Order By: Relevance
“…This confirms the results of two studies [30,31], which reported that these conditions did not have any influence on the physical benefits of cardiac rehabilitation.…”
Section: Determinantssupporting
confidence: 90%
“…This confirms the results of two studies [30,31], which reported that these conditions did not have any influence on the physical benefits of cardiac rehabilitation.…”
Section: Determinantssupporting
confidence: 90%
“…[1][2][3][4][5][6][7] Exercise training in patients with chronic atrial fibrillation (AF) has, however, received less attention. [8,9] We have recently studied the effects of physical training on heart rate and atrioventricular conduction in patients with AF [11]. No previous study has investigated the effects of exercise training on healthrelated quality of life (HRQoL) in patients with chronic AF.…”
Section: Introductionmentioning
confidence: 99%
“…These hemodynamic and thromboembolic consequences of AF may therefore explain the increased risk of traffic accidents among patients with AF compared with matched non-AF individuals. The finding that AF patients were less likely to be involved in motorcycle accidents but more likely to have a traffic accident as a pedestrian may reflect the relatively limited ability of these patients [27][28][29][30] to utilize vehicles such as motorcycles and scooters which require skill and balance, who might then instead opt for an easier method of covering short distances, i.e. walking.…”
Section: Incidence and Presentations Of Traffic Injury In Patients Wimentioning
confidence: 99%
“…limited outdoor activity and therefore less demand for traffic transportation among more senior individuals, who are more likely to have physical and mental diseases of old age, might explain this finding [27][28][29][30]34]. Another presumption might be that driving behavior changes with age, such as driving more slowly and cautiously as well as tending to choose shorter and safer routes, which could mitigate risk of accident as well, awaiting further study.…”
Section: Risk Factors Of Traffic Accidents In Af Patientsmentioning
confidence: 99%